2000
DOI: 10.1074/jbc.275.13.9178
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2 Is Involved in the Mitogenic Activity and Signaling of Granulocyte-Macrophage Colony-stimulating Factor in Osteoblasts

Abstract: We previously showed that granulocyte-macrophage colony-stimulating factor (GM-CSF) binds to heparan sulfate proteoglycans expressed at the surface of osteoblastic cells and that the mitogenic activity of this cytokine is dependent on the presence of fully sulfated proteoglycans. In this study, we determined if GM-CSF interacts with syndecans, a family of cell surface heparan sulfate proteoglycans. Human primary osteoblasts were found to express syndecan-2 and -4 but few syndecan-1 transcripts and proteins. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…SDC2 is a significant upstream regulator of the TGF-ß signaling pathway (6), regulating signaling by acting as a co-receptor for growth factors. SDC2 facilitates signaling by forming a ternary complex with TGF-ß and its signaling receptors, TGFRI and TGFRII (7)(8)(9). This protein plays diverse roles in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…SDC2 is a significant upstream regulator of the TGF-ß signaling pathway (6), regulating signaling by acting as a co-receptor for growth factors. SDC2 facilitates signaling by forming a ternary complex with TGF-ß and its signaling receptors, TGFRI and TGFRII (7)(8)(9). This protein plays diverse roles in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Syndecan-2 is involved in regulation of cell adhesions in several cell lines including epithelial cells (20 -22), neuronal cells (23,24), and mesenchymal cells (25). Compared with syndecan-1 and -4, the role of syndecan-2 in cell migration has been less investigated.…”
mentioning
confidence: 99%
“…Compared with syndecan-1 and -4, the role of syndecan-2 in cell migration has been less investigated. However, several reports indicate that syndecan-2 may positively regulate cell migration, since syndecan-2 is normally highly expressed in cells under migratory conditions (22,24,25). In particular, in Lewis lung carcinoma-derived P29 cells, syndecan-2 plays a major role in the interaction with fibronectin and regulates actin stress fiber formation in cooperation with integrin ␣ 5 ␤ 1 (22).…”
mentioning
confidence: 99%
“…It has been suggested that syndecan-4 regulates protein levels of the endothelial growth factor receptor (erb-B2 and -B3) in a colon cancer cell line (40). Functional interactions between syndecan-2 and GM-CSF in osteoblasts have been suggested; perhaps syndecan-2 also plays a role as a co-receptor for this cytokine (41). Moreover, syndecan-2 can bind and regulate the signaling of tumor growth factor-ß, and the binding is through the ectodomain of the core protein, with the heparan sulfate chains having only a minor role.…”
Section: Syndecans and Growth Factor Signalingmentioning
confidence: 99%